High prevalence of GB Virus C/Hepatitis G Virus RNA among Brazilian blood donors - José Eduardo Levi; Daniela Gazoto Contri; Liliam Pereira Lima; Deise Tihe Takaoka; Regina Helena Garrini; Wellingtom Santos; Roberta Fachini; Silvano Wendel (Universidade de São Paulo (USP), 2003)
The aim of this study was to investigate the presence of the Hepatitis G Virus on a population of blood donors from São Paulo, Brazil and to evaluate its association to sociodemographic variables. Two RT-PCR systems targeting the putative 5'NCR and NS3 regions were employed and the former has shown a higher sensitivity. The observed prevalence of HGV-RNA on 545 blood donors was 9.7% (CI 95% 7.4;12.5). Statistical analysis depicted an association with race/ethnicity, black and mulatto donors being more frequently infected; and also with years of education, less educated donors presenting higher prevalences. No association was observed with other sociodemographic parameters as age, gender, place of birth and of residence. DNA sequencing of nine randomly chosen isolates demonstrated the presence of genotypes 1, 2 and 3 among our population but clustering of these Brazilian isolates was not detected upon phylogenetic analysis.